CD30 expression in cutaneous B-cell and post-transplant peripheral T-cell lymphoma: report of 2 cases - Albrecht, Hana; Woodroof, Janet M; Reyes, Ruben; Powers, Benjamin C; Fraga, Garth R (Dermatology online journal, 2014)
CD30 expression is the hallmark of the cutaneous CD30+ lymphoproliferative disorders, lymphomatoid papulosis and anaplastic large cell lymphoma. We report CD30 expression in cutaneous follicle center cell lymphoma and in cutaneous post-transplant peripheral T-cell lymphoma. Histopathologists should be aware of CD30 expression in cutaneous lymphomas outside the realm of so-called CD30+ lymphoproliferative disorders to avoid diagnostic errors and improper medical treatment.